Categorical Data Analysis: The Log Linear Model - Stevens, James P. (Applied Multivariate Statistics for the Social Sciences, 2009)
The.reader.may.recall. from. introductory.statistics. that.one.of. the.most.elementary.statistical. tests. is. the. two-way.chi. square..This. test. is. appropriate. if. the. subjects,.or.more. generally,.entities,.have.been.cross-classified.in.two.ways.and.the.data.is.in.the.form.of. frequency.counts..As.an.example,.suppose.we.have.taken.a.sample.of.66.adults.and.wish.to. determine.whether.sex.of.adults.is.related.to.their.approval.or.lack.of.approval.of.a.television.series..The.results.are.as.follows:The.null.hypothesis.for.a.two-way.chi-square.is.that.the.modes.of.classification.are.independent..In.this.case.we.have: Ho:.Sex.is.independent.of.approval.of.the.television.series..Based.on.the.null.hypothesis,.